Adobe Encore DVD : in the studio - Dixon, Douglas (O'Reilly digital studio., 2004)
If you're looking for an easy and stimulating way to master Adobe Encore DVD and fine-tune your moviemaking skills at the same time, look no further than Adobe Encore DVD: In the Studio . This full-color tutorial will help you push the limits of Adobe Encore DVD by helping you to create highly imaginative designs and projects. Designed primarily for Adobe Creative Suite developers, particularly those using Adobe Premiere and AfterEffects, as well as filmmakers who wish to transfer their projects to DVDs, the book combines practical learning materials and project-based lessons. But Adobe Encore DVD: In the Studio is not your average tutorial. The book draws on the experience of author Doug Dixon--an expert on Adobe Encore DVD, the author of other books on DVD development, and a core member of the product's alpha and beta programs. Well-versed in both the use and design of Adobe Encore DVD, Dixon imbues this O'Reilly Media digital book with the unique perspective of an insider who really knows his pixels. Adobe Encore DVD: In the Studio discusses the protocols involved with DVD files and file systems; pixel aspect ratio issues; common gotchas using both still and motion media; and a plethora of tips and tricks to using dynamic buttons. You'll get up to speed on importing from Photoshop and AfterEffects, making motion video menus available, and looping video and audio. You'll also learn about adding multilingual menus and subtitles, encoding rules, scripting, and even placing Easter eggs in a DVD! By studying this comprehensive, hands-on tutorial, you will be able to quickly and efficiently develop professional-looking DVDs studded with special effects worthy of a Hollywood studio.